Expectation and student satisfaction for the academic service of the Private University of Tacna in 2015 - Eyzaguirre Reinoso, Omar Alberto (2016)
Objective: The objective of the research was to determine the relationship between expectation and student satisfaction with academic service provided by the Private University of Tacna academic development during 2015. Method: This research is of basic type. The research problem corresponds to a descriptive design - correlational. The research was conducted at the Private University of Tacna in the period of the academic year 2015. Units of study were students of the Private University of Tacna. The population consisted of 5,289 students enrolled in the Private University of Tacna in 6 faculties and 20 runs. The sample consists of 350 students, the calculated sample size table Fisher - Arkin - COLTON a + - 5% margin of error. We worked with the survey as a technique to establish the levels of expectations and satisfaction of students study subjects. The instruments to collect information were: Questionnaire 1 to 17 collect information on the level of expectation of students and 2 for satisfaction questionnaire. Results: According to the study considers dimensions. It can be seen that most students are placed in a moderate expectation except for professional pre practical dimension, where most are located in the category low expectation. However, it should be mentioned that high expectations for these dimensions are below the 30.00% of students study subjects. Regarding the variable student satisfaction, it can be noted that most students are placed in the category moderate satisfaction. Punctually it is noted that the university infrastructure and services is aroused greater satisfaction, while university life is located on the opposite side. However, it is necessary to mention that satisfaction in these dimensions is below 23.43% of students study subjects.